வா. மு. கோமு சிறுகதைகள் காட்டும் பண்பாட்டு மீறல்கள் / Cultural Violation shown in the Short Stories of Vaa. Mu. Komu - அ. சதிஸ்குமார் / A. Sathishkumar (International Journal of Tamil Language and Literary Studies)
Culture and knowledge have played key role in search of man’s social development and both are very essential. In Tamil culture, customs, rituals, caste, gender relations, worship and festivals have been closely associated with life and they are followed by the people since ages. The short stories of Va.Mu.Komu are not just a collection of information but express the factors of human life, culture and social setting in his works. He is a writer who speaks about the cultural heritage and records the cultural changes and transformation of the Tamil people. Cultural changes often occur while ignoring customs that are followed in God worshipping since ancient times. By influencing and changing certain customs in sacrifice in temple festivals due to economic growth, the caste ideology created for the marginalized people by people belonging to higher caste avoids significant customs and rituals in view of chaotic situations that arise in family life and accept modernized language and dress. He beautifully portrays the culture of the people living in a rural environment in his works. He shows their cultural elements such as beliefs, customs, worship, religion, and caste in his short stories and he speaks strongly about the violations of those cultures. When cultural violations occur, the society faces various problems. The purpose of this article is to examine the benefits and harms caused to humanity and the social change caused by those cultural violations.